Updated emm-typing protocol for Streptococcus pyogenes. (July 2020) - Frost, H.R.; Davies, M.R.; Velusamy, S.; Delforge, V.; Erhart, A.; Darboe, S.; Steer, A.; Walker, M.J.; Beall, B.; Botteaux, A.; Smeesters, P.R.
Abstract: Objectives: PCR-based typing of the emm gene Streptococcus pyogenes often results in the amplification of multiple bands. This has resulted in the misclassification of strains into types based on non- emm gene sequences. We aimed to improve the specificity of the emm typing PCR reaction using a primer called CDC3, the sequence for which has been previously used to identify emm genes in silico. Methods: The proposed primer CDC3 was validated in silico from a global database of 1688 GAS genomes and in vitro with 32 isolates. PCR reactions were performed on genomic DNA from each isolate, using the published CDC1 forward primer with the CDC2 reverse primer or the new CDC3 reverse primer. The products were examined by gel electrophoresis, and representative PCR products were sequenced. Results: In 1688 S. pyogenes genomes, the previous CDC2 reverse primer annealed in silico in 1671 emm genes and also in 2109 non emm genes in close proximity, whereas the new CDC3 primer annealed in 1669 emm genes only. The remaining 19 genes without a CDC3 binding site were chimeric emm genes. The PCR pair CDC1+CDC3 produced a single band at appropriate molecular weight in all 32 isolates tested, while the CDC1+CDC2 pair produced more than one band in 13 of 32 isolates (40%). Conclusions: The new CDC3 primer is more specific for emm genes than the previous CDC2 primer and represents a simple solution to reduce the potential for mistyping S. pyogenes strains.